Destiny and deliberation essays in philosophical theology - Kvanvig, Jonathan L. (Oxford University Press, 2011)
Organized thematically by the endpoints of time, the volume begins by addressing eschatological matters--the doctrines of heaven and hell--and ends with an account of divine deliberation and creation. Kvanvig develops a theistic outlook which reconciles a traditional, high conception of deity, with full providential control over all aspects of creation, with a conception of human beings as free and morally responsible. The resulting position and defense is labeled "Philosophical Arminianism." -- From publisher.